Letter (copy) : Potatoes for Spain - Tewson, Vincent
032-0082-001 International HVT/AC/153 F.I. de Sol. 508 18th March, 1939. Mr. W. Schevenels, International Federation of Trade Unions, 9, avenue d'Orsay, PARIS VIIe. Dear Comrade Schevenels, POTATOES FOR SPAIN. Thank you for your letter of 17th March. I note the reason why you desired to know the price of the potatoes shipped from this country to France. I presume the main consignment went through, and that the quantity in question is merely the 33 tons which could not be got through on the first boat. I hope that an arrangement has not been finally settled with the French authorities in regard to price, as I find that the cost c.i.f. Rouen was 45/8 per ton. Had I known the reason for this inquiry, I would of course have informed you of this in the first place, but I thought it was merely an inquiry as to possible further supplies. In my letter of 14th March, I explained that freight charges to Rouen were additional. I certainly think that any settlement should be on the basis of the figure which we have actually paid. In accordance with your request, I am enclosing a copy of the invoice which we received for the full consignment, of which the 33 tons was merely the completion of the order. Yours faithfully, Assistant Secretary. copy invoice 292/946/32/82